ANALISIS FAKTOR LINGKUNGAN EKSTERNAL DAN INTERNAL USAHA SAYUR ORGANIK (STUDI KASUS PADA UD. EKA SETIA LESTARI DI BATURITI) - Javandira, Cokorda; Gama, Agus Wahyudi Salasa (JUIMA : JURNAL ILMU MANAJEMEN, 2018)
UD. Eka Setia Lestari is a business that is engaged in agriculture. The resulting product is an organic vegetable. Currently the change of community life for health is an opportunity for organic vegetable business. Analysis of internal and external environmental conditions is needed to provide an overview of the company's position and find solutions for companies to compete and still exist. Based on the analysis of internal and external environment of UD. Eka Setia Lestari is in an average position. There needs to be improvements on the internal and external side of the company in order to improve its position for the better.